Visual Technology Development for Arabic Learning Based on ADDIE Development Model - Haniah, Haniah; Jumadil, Jumadil (Jurnal Al-Maqoyis, 2022)
This article aimed to determine the variety of visual technology and its development in learning Arabic. Visual technologies that could be used by Arabic language teachers were all kinds of media that could be used in general learning, both in the form of non-projected visual media and projected visual media, Non-projected visuals in the form of graphic media, realia (real objects), and models,  while visual media that could be projected are LCDs, and digital cameras. In its development, Arabic learning could be developed with various models, one of which is the development of the ADDIE (analyze, design, development, implementation, and evaluation), ADDIE Development model was media development through the following steps: Analyse, Design, Develop, Implement, and Evaluate. Visual technology for learning Arabic was developed by first analyzing the needs of students, then designing and developing the right media (production process), then socializing it to students, and finally evaluating it. If it had been completed, visual technology could be implemented in the learning classroom